2022
DOI: 10.3390/polym14061252
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic and Synthesis of High-Temperature Resistant Liquid Crystal Epoxy Resin Containing Boron Nitride Composite

Abstract: Five liquid crystal epoxy resins and composites containing flat boron nitride (f-BN) and spherical boron nitride (s-BN) were successfully synthesized. The chemical structures, crystal diffraction, and thermal conductivity of the liquid crystal (LC) epoxy composites were measured using Nuclear Magnetic Resonance (NMR), Differential Scanning Calorimetry (DSC), X-ray, and Discovery Xenon Flash. In this study, the molecular arrangement of five LC epoxy resins and the thermal conductivity of their composites were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…As the quantity of this compound within the LC matrix rises, the composite's glass transition temperature escalates, accompanied by a notable increase in the thermal conductivity coefficient (λ). This is the result of controlled phonon scattering in the epoxy resin [75][76][77][78][79]. Its molecular orientation enables efficient heat transfer through phonon vibrations.…”
Section: Inorganic Fillersmentioning
confidence: 99%
“…As the quantity of this compound within the LC matrix rises, the composite's glass transition temperature escalates, accompanied by a notable increase in the thermal conductivity coefficient (λ). This is the result of controlled phonon scattering in the epoxy resin [75][76][77][78][79]. Its molecular orientation enables efficient heat transfer through phonon vibrations.…”
Section: Inorganic Fillersmentioning
confidence: 99%
“…used 4,4′‐bis(4‐hydroxybenzyl) diaminophenyl diglycidyl ether (SBPDAE), cationic initiator (BMIM), and spherical BN (s‐BN) fillers to prepare the corresponding s‐BN/SBPDAE composites. When the amount of s‐BN was 60 vol%, the λ of s‐BN/SBPDAE composites was 9.36 W/(m·K), 45.8 times higher than that of pure epoxy resin (0.20 W/(m·K)) 25 . However, the introduction of excessive thermally conductive fillers would lead to high interfacial thermal resistance, resulting in severe phonon scattering, which is not conducive to improving the λ value 26 .…”
Section: Introductionmentioning
confidence: 98%
“…When the amount of s-BN was 60 vol%, the λ of s-BN/SBPDAE composites was 9.36 W/(m⋅K), 45.8 times higher than that of pure epoxy resin (0.20 W/(m⋅K)). 25 However, the introduction of excessive thermally conductive fillers would lead to high interfacial thermal resistance, resulting in severe phonon scattering, which is not conducive to improving the λ value. 26 Additionally, due to relatively high ε value (>4.0) of the thermally conductive fillers, the final ε values of the epoxy composites are often high.…”
Section: Introductionmentioning
confidence: 99%
“…18 Wu et al showed that the thermal conductivity of the SBN composites was better than that of flat BN composites. 19 However, there are few studies on the thermal conduction, electrical insulation, and flame-retardant properties of the SBN-enhanced polymer composites, especially in the case of high-voltage discharge. In this paper, densified epoxy-SBN composites were prepared using multiscale SBN as fillers.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Ren et al prepared SBN/polydimethylsiloxane composites using a spray-assisted self-assembly method with a thermal conductivity of 2.30 W m –1 K –1 . Wu et al showed that the thermal conductivity of the SBN composites was better than that of flat BN composites . However, there are few studies on the thermal conduction, electrical insulation, and flame-retardant properties of the SBN-enhanced polymer composites, especially in the case of high-voltage discharge.…”
Section: Introductionmentioning
confidence: 99%